Rola wychowania fizycznego w budowaniu świadomości w zakresie aktywności fizycznej uczniów Gimnazjum im. Jana Pawła II w Mroczy = The role of physical education to build awareness of physical activity students Gymnasium named John Paul II in Mrocza - Jędrzyńska, Agata; Szark-Eckardt, Mirosława; Kuska, Michalina; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Jędrzyńska Agata, Szark-Eckardt Mirosława, Kuska Michalina, Zukow Walery. Rola wychowania fizycznego w budowaniu świadomości w zakresie aktywności fizycznej uczniów Gimnazjum im. Jana Pawła II w Mroczy = The role of physical education to build awareness of physical activity students Gymnasium named John Paul II in Mrocza. Journal of Education, Health and Sport. 2015;5(9):317-336. ISSN 2391-8306. DOI10.5281/zenodo.30926 http://dx.doi.org/10.5281/zenodo.30926 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A317-336 https://pbn.nauka.gov.pl/works/624239 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 08.09.2015. Rola wychowania fizycznego w budowaniu świadomości w zakresie aktywności fizycznej uczniów Gimnazjum im. Jana Pawła II w Mroczy The role of physical education to build awareness of physical activity students Gymnasium named John Paul II in Mrocza Agata Jędrzyńska1, Mirosława Szark-Eckardt2, Michalina Kuska2, Walery Zukow2 1Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Instytut Geografii 2Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Instytut Kultury Fizycznej Streszczenie Tematem pracy jest wpływ uczestnictwa w zajęciach wychowania fizycznego na proces budowania świadomości w zakresie aktywności fizycznej. Badana grupa to uczniowie klas trzecich Gimnazjum im. Jana Pawła II w Mroczy. Celem, jaki przyświecał podjęciu tego tematu było zbadanie, w jakim stopniu uczestnictwo w zajęciach wychowania fizycznego wpływa na ogólny rozwój młodego człowieka w określonym wieku szkolnym oraz określenie stosunku nastolatków do podejmowania aktywności fizycznej. W przypadku uczniów klas trzecich gimnazjum – a założyć można, że problem dotyczy także pozostałych poziomów nauczania – duża część uczniów rezygnuje z czynnego udziału w lekcjach wf, najczęściej z błahych powodów. Nakłada się to na okres dojrzewania, a więc trudny czas dla uczniów pod względem zmian zachodzących w ich psychice. To także trudny czas dla rodziców i wychowawców, wymagający od nich znacznej uwagi i zrozumienia źródeł zachowań młodych ludzi. Wychowanie fizyczne bez wątpienia ma ogromne znaczenie w ogólnym procesie wychowawczym. Dlatego ważne jest, by na poszczególnych szczeblach edukacji uczniowi nabyli pożądane nawyki w zakresie aktywności fizycznej i świadomości prozdrowotnej, gdyż w późniejszym życiu, w przypadku zaniedbań w tym obszarze, trudniej będzie je w sobie wzbudzić. Z przeprowadzonych analiz można wywnioskować, że młodzież ma w sobie potencjał fizyczny i intelektualny, by w dorosłym życiu być aktywnymi i zdrowymi ludźmi. Jednak warunkiem tego jest świadome kreowanie nawyków, które w przyszłości będą to warunkować. Słowa kluczowe: wychowanie fizyczne, aktywność fizyczna, kultura fizyczna, świadomość, edukacja, styl życia, zdrowie. Abstract The theme of the work is the impact of participation in physical education classes on the process of building awareness of physical activity. The test group is a third grade students Gymnasium named John Paul II in Mrocza. The goal, which prevailed during the adoption of this theme was to examine the extent to which participation in the classes of physical education affects the overall development of a young man in a particular school and the determination of the ratio of teenagers to make physical activity. In the case of third-country students in grades Gymnasium – and you can bet that the problem also applies to the other levels of learning – a large part of students resigns from active participation in lessons of wf, the most trivial of reasons. Imposes on puberty, so a tough time for students in terms of changes in their psyche. It’s also a difficult time for parents and educators, requires them to substantial attention and understanding the sources of the behavior of young people. Physical education no doubt is of the utmost importance in the overall educational process. Therefore, it is important that the various levels of education the student in terms of physical activity habits desirable bought and awareness of preventive treatment, because later on in life, in the case of neglect in this area, it will be harder in itself arouse. From the analysis it can be concluded that young people have the potential physical and intellectual, to adulthood to be active and healthy people. However, this condition is conscious of creating habits that in the future it will be condition. Keywords: physical education, physical activity, physical culture, consciousness, education, lifestyle, health.